Rough Notes of a Journey through the Wilderness, from Trinidad to Pará, Brazil By Way of the Great Cataracts of the Orinoco, Atabapo, and Rio Negro - Wickham, Henry Alexander 1846-1928 (Cambridge library collection. Botany and horticulture, 1872)
Sir Henry Alexander Wickham (1846–1928) is remembered for his role in bringing the seeds of the rubber tree in 1876 from Brazil to the Royal Botanic Gardens at Kew, where seedlings were successfully cultivated and then sent to Asia for the establishment of commercial plantations. Wickham later styled his actions in collecting some 70,000 seeds as a tale of botanical smuggling, though at the time such action was not illegal. Skilled as a self-publicist, he enjoyed the great acclaim of the rubber industry as it burgeoned in British colonies abroad. This account, first published in 1872, is of Wickham's earlier travels in South America. The first part of the work traces his journey by river into the continent, recording his observations on rubber cultivation in Brazil. The second part describes his time among the indigenous peoples who lived on the Caribbean coast of Central America